2019
DOI: 10.3390/ijms20194795
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Li, et al. Conserved miR396b-GRF Regulation Is Involved in Abiotic Stress Responses in Pitaya (Hylocereus polyrhizus). Int. J. Mol. Sci. 2019, 20, 2501

Abstract: The authors wish to make the following corrections to this paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The miRNAs we considered in this study have previously been identified in other plant species as playing a role in hybridization [ 59 ], growth regulation [ 60 , 61 , 62 , 63 ] and in response to various biotic and abiotic stresses including nutrient deficiency, drought, cold and salinity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Moreover, miRNAs of the miR396 family are known to target oxidases, including cytochromes involved in xenobiotic detoxification [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs we considered in this study have previously been identified in other plant species as playing a role in hybridization [ 59 ], growth regulation [ 60 , 61 , 62 , 63 ] and in response to various biotic and abiotic stresses including nutrient deficiency, drought, cold and salinity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Moreover, miRNAs of the miR396 family are known to target oxidases, including cytochromes involved in xenobiotic detoxification [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several studies have shown that flavonols are required for male fertility and more specifically for the pollen tube growth [ 26 - 28 ]. Also, it has been demonstrated that flavonoid biosynthesis pathway is involved in the process of forming the pollen coat in various plant species such as Arabidopsis, Brassicas and cotton [ 38 - 41 ]. Ingrosso et al [ 42 ] over-expressed the stilbene synthase gene in tomato and obtained a complete male sterility due to significant impairment in the flavonoid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…GRF genes encode transcription factors that bind to sequence-specific DNA, which interacts with the transcriptional cofactor GRF-INTERACTING FACTOR (GIF) to form functional transcriptional complexes that regulate cell proliferation to control leaf size ( Kim et al, 2003 , 2022 ; Kim and Kende, 2004 ; Horiguchi et al, 2005 ; Lee et al, 2009 ; Wang et al, 2011 ; Debernardi et al, 2014 ; Lee and Kim, 2014 ; Lu et al, 2020 ). GRF is negatively regulated by microRNA (miR396), and its expression is suppressed by miR396 after transcription ( Wang et al, 2011 ; Baucher et al, 2013 ; Debernardi et al, 2014 ; Liu et al, 2014 , 2021 ; Li et al, 2019 ; Szczygiel-Sommer and Gaj, 2019 ; Liebsch and Palatnik, 2020 ; Beltramino et al, 2021 ; Lu et al, 2021 ; Pegler et al, 2021 ; Kim et al, 2022 ). GRF/GIF has a universal growth-promoting effect on inflorescences and flower organs of several species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, loss of GRF and GIF function usually leads to varying degrees of sterility in plants, flower organ fusion, and disturbances in the number of flower organs ( Wu et al, 2014 ; Zan et al, 2020 ). Some GRFs also play an important role in abiotic stress response, including cold and salt stress ( Kim et al, 2012 ; Khatun et al, 2017 ; Wallace et al, 2017 ; Shang et al, 2018 ; Li et al, 2019 , 2021 ; Cao et al, 2020 ; Pegler et al, 2021 ). In soybean, the transcription of all GRFs was affected by shading.…”
Section: Introductionmentioning
confidence: 99%